(untitled) (Research, Society and Development, 2020)
The cardiac plexus is a vast network of neurons grouped into ganglia distributed throughout the myocardium. The epicardial adipose tissue covers the heart performing important functions, such as, lipid storage. However, its exaggerated expression might represent a risk factor, which can be prevented by the practice of physical activities that improves the heart contractile propulsive capacity. Insulin has been used in association with physical exercise so as to increase muscle mass and improve physical performance. Both insulin and exercise have been evidenced due to their neurotrophic effects. The purpose of this study was to ascertain whether insulin associated with resistance training could structurally modify the cardiac plexus and epicardial adipose tissue. Four groups (n = 6) of male Swiss mice were used: non-trained saline, non-trained insulin; trained saline; trained insulin. The training was performed on a vertical ladder at 90% of the maximum load, 3 times/week for 8 consecutive weeks. After the experimental period, the hearts of the animals were removed, and 5-μm sections were stained with Hematoxylin/Eosin, Giemsa and Picrossirius in order to evaluate the structures of the cardiac plexus. There was no significant difference with regard to the area and the total number of neurons, nor to the area with collagen. However, whereas insulin administration hypertrophied the adipocytes and predisposed an inflammatory environment, physical exercise played an anti-inflammatory role. As a conclusion, it is worth mentioning that resistance training did not change the cardiac plexus, however the epicardial adipose tissue was reduced, an effect antagonized by insulin.